(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study examines the pivotal role of tribal communities in the economic development of Madhya Pradesh, with a specific focus on Betul district. With 42.34% of the population belonging to Scheduled Tribes, Betul represents a significant case study for understanding tribal economic contributions. The research adopts a management perspective to analyze how tribal communities contribute